Management of HIV in Children Using a Bovine Colostrum-Based Food Product— An Observational Field Study - Odong, Patrick Olwedo; Angwech, Pamela Judith; Obol, James; Kuule, Julius; Florén, Claes-Henrik (World Journal of AIDS, 2015)
Malnutrition increases the severity and mortality of HIV infection. Therefore, this field study was started and aimed to provide a major cohort of HIV-infected children with the colostrum- based food product ColoPlus (ColoPlus AB, Malmö, Sweden) and to investigate the effects of ColoPlus on the nutritional status and immunological capacity of children including tolerability and safety of the product. Methods: In this major field program comprising 850 malnourished HIV positive children, 50 grams of ColoPlus was administrated for 4 weeks as the first meal in selected health facilities in Northern Uganda. Forty-eight of these children (8 months - 14 years of age) were recruited into a descriptive prospective study and were followed for 12 weeks. At the start (week 0) and at weeks 4, 8 and 12, CD4+ cell counts, serum albumin and hemoglobin were analyzed. The remaining 802 patients were observed to register safety and tolerability of ColoPlus. Results: There was a general improvement of wellbeing of the children with increased body weight and decreased fatigue. In the descriptive study of the 48 children, there was a significant rise of the CD4+ values at week 4 (+15.4% ± 2.8%, p = 0.0001) compared to week 0, and at week 8 (+39.1% ± 3.9%, p < 0.0001), but a return towards the 0-values at week 12 (+2.1%, ±2.8%, NS). Hemoglobin and serum albumin showed an almost similar trend. ColoPlus was well tolerated by all the 850 children and no side effects or adverse events were seen. Conclusion: These results show that addition of a colostrum-based food product to the daily diet is beneficial in HIV-positive malnourished children. An improvement in nutritional status as well as in immune capacity was seen. These effects were prolonged and remained at least 4 weeks after cessation of ColoPlus administration.
Keywords: CD4+; Bovine Colostrum; Colostrum-Based Food Supplement; HIV Infected Children